The Existence of Local-Owned Enterprises in the Regional Financial Management System in Indonesia - Zainal Abidin Pakpahan (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
Regional-owned enterprises or abbreviated as BUMD are companies that are engaged in managing regional finances as a supporter of the nation's economy at the regional level which actually needs to be considered as their existence considering that currently BUMD is a central issue when legally it starts to appear to be a little weak as a result of regulations that have just visited yet. after being promulgated by the legislature, because the old regulations were inadequate with the current developments in the globalization era, starting from the sophistication of electronics that allowed companies to actually align them so that they could be more advanced and adapt according to their circumstances to be more advanced and developing,therefore the old regulations are no longer enforced resulting in a legal vacuum in running the organizational wheels of the company's institutions. Keynote: Existence, Local-Owned Enterprises, Management, Finance, Indonesia.